Recognition And Legitimation Of Ill-Wed Children According To Khi And The Civil Code And Law No. 1 Of 1974 - Muhammad Firmansyah; Ali Rahmadi Batubara; Ilham Maylandi S Damanik; Meldyana Permata Abdillah (ISNU Sumatera Utara, 2025)
This paper discusses the recognition and legitimation of illegitimate children according to the Compilation of Islamic Law (KHI), the Civil Code (KUHPerdata), and Law No. 1 of 1974 concerning Marriage. According to the KHI, illegitimate children can be recognized by their biological father through acknowledgment, but with limitations on inheritance rights. The Civil Code provides broader regulations, where illegitimate children recognized by their father through formal recognition or a court decision are entitled to certain rights, including inheritance rights. Meanwhile, Law No. 1 of 1974 emphasizes the importance of protecting children in legal marriages, although specific regulations regarding illegitimate children are more limited. This study aims to identify differences and similarities in the regulations regarding the recognition and legitimation of illegitimate children, as well as their impact on the rights of these children in the context of Indonesian law.